Cetrimonium bromide and potassium thiocyanate assisted post-vapor treatment approach to enhance power conversion efficiency and stability of FAPbI3 perovskite solar cells. Issue 2 (5th January 2023) - Kumar, Anjan; Singh, Sangeeta; Sharma, Dilip Kumar; Al-Bahrani, Mohammed; Alhakeem, Mohammed Ridha H.; Sharma, Amit; Anil Kumar, T. Ch.
Abstract : Vapor treatment approach to enhance the power conversion efficiency and stability of FAPbI3 based perovskite solar cell. Abstract : Formamidinium lead iodide (FAPbI3 ) is the most promising perovskite material for producing efficient perovskite solar cells (PSCs). Here, we develop a facile method to obtain an α-phase FAPbI3 layer with passivated grain boundaries and weakened non-radiative recombination. For this aim, during the FAPbI3 fabrication process, cetrimonium bromide + 5% potassium thiocyanate (CTABr + 5% KSCN) vapor post-treatment is introduced to remove non-perovskite phases in the FAPbI3 layer. Incorporation of CTA + along with SCN − ions induces FAPbI3 crystallization and stitch grain boundaries, resulting in PSCs with lower defect losses. The vapor-assisted deposition increases the carriers' lifetime in the FAPbI3 and facilitates charge transport at the interfacial perovskite/hole transport layer via a band alignment phenomenon. The treated α-FAPbI3 layers bring an excellent PCE of 22.34%, higher than the 19.48% PCE recorded for control PSCs. Besides, the well-oriented FAPbI3 and its higher hydrophobic behavior originating from CTABr materials lead to improved stability in the treated PSCs.